Reconciling theories of a mechanically driven meridional overturning circulation with thermohaline forcing and multiple equilibria - Johnson, H; Marshall, D; Sproson, D (2007)
It has recently been suggested that the structure and strength of the meridional overturning circulation in the global ocean is governed by the input of mechanical energy to the system by winds and tides. However, it is not clear how this suggestion relates to the existence of multiple equilibria of the meridional overturning circulation, which depends on thermohaline feedbacks and is more consistent with a buoyancy-driven view of the circulation. Both theories have been illustrated by box models in the past (Stommel in Tellus 13:224-230, 1961 Gnanadesikan in Science 283:2077-2079, 1999. Here we incorporate these two theories into a single box model in an attempt to reconcile the roles of mechanical and buoyancy forcing in driving the meridional overturning circulation. The box model has two equilibrium solutions, one with sinking at high northern latitudes as in the present-day Atlantic, and one without. The circulation is mechanically driven, but the northern sinking can be thought of as a release valve which acts as a sink of potential energy when the surface water at high northern latitudes is dense enough to convect. While the source of energy comes from mechanical forcing, the presence or otherwise of multiple equilibria is therefore determined by thermohaline feedbacks. In some areas of parameter space an oscillation between the model's two circulation regimes occurs, reminiscent of a bipolar seesaw. © Springer-Verlag 2007.